(untitled) (Development Service Industry Management, 2025)
In the context of globalization and the rapid advancement of digital technologies, the global economy is undergoing profound transformations that significantly impact the operations of enterprises across various industries. Digitalization has emerged as a key driver of change, offering new opportunities to improve business process efficiency, create innovative products and services, and strengthen competitive market positions. For Ukrainian businesses, digital transformation is not only a challenge but also a crucial condition for qualitative growth, enabling effective responses to external challenges and the utilization of cutting-edge technological advancements. The implementation of digital solutions facilitates the optimization of production and management processes, cost reduction, increased customer orientation, and organizational flexibility. However, this transformation process also presents several challenges, such as limited financial resources, insufficient staff training, resistance to change, and shortcomings in the regulatory environment. Therefore, studying the mechanisms for developing innovative business strategies in the digital age is especially relevant. The aim of this article is to analyze the theoretical and practical aspects of forming innovation-driven development strategies for enterprises amid digital transformation. The authors examine current digitalization trends, including automation, cloud technologies, the Internet of Things (IoT), blockchain implementation, and the growing use of digital platforms, particularly in e-commerce. Considerable attention is given to the historical evolution of innovation strategies — from a focus on technological improvements to the creation of new business models and flexible organizational structures. The paper outlines key challenges facing Ukrainian enterprises in their digital transformation journey and highlights promising prospects, such as increased government support, access to international innovation funding programs, and the growth of startup ecosystems. The article proposes ways for enterprises to adapt to new conditions through investment in digital culture, personnel training, and the adoption of successful international practices. This will help ensure long-term competitiveness and integrate Ukrainian businesses into global digital processes.